Customer Bonding, Customer Satisfaction, and Customer Loyalty (Study on the Customer of “SMEs Martabak Hokky Kawanua” on Tondano) - Steven Set Xaverius Tumbelaka; Jenny Nancy Kaligis; Ericson Mengga (International Journal of Applied Business and International Management, 2022)
This research was conducted on Martabak Hokky SME customers in Tondano city, with the aim of knowing how the level  of influence of Customer Bonding to Customer Loyalty, and  the influence of Customer Satisfaction to Customer Loyalty, especially in the SMEs  we studied, in addition to that, this research will also look at the  joint influence of Customer  Bonding and Customer Satisfaction on Customer Loyalty from the SMEs studied.  Quantitative method with multiple regression analysis is the method and analysis that is the choice to be used in this study, by taking a sample of  1 10 people. The findings from the  multiple analysis test obtained from the  study, show that  there is a significant effect of Customer Bonding to Customer Loyalty, it can be explained that  good Customer Bonding will help increase Loyalitas Customer significantly.  The  next result also shows a partially significant influence of Customer Satisfaction to Customer Loyalty, so it can be said that if Customer Satisfaction increases, it will also increase Loyalty as Customers significantly as well, The final results of the study show  The simultaneous significant influence from Customer Bonding and Customer Satisfaction to Customer Loyalty from SMEs studied in this study, in other words,  the increase in customer loyalty is strongly influenced by the better  Customer Bonding and Customer Satisfaction.  It can be suggested to the manager of Martabak UKM Hokky Kawanua to be able to pay better attention to how to maintain Customer Bonding and Customer Satisfaction in order  to be able to continue to form loyalty from strong customers, so that customers will continue to buy  products, and for further research to be able to see and test more deeply about customer loyalty by paying attention to other variables that were not studied in this study.